Innovation Program of the Indonesian Mosque Youth Communication Agency in Increasing the Participation of Mosque Youth - Qowigun Maajid; Faridah Faridah (Sekolah Tinggi Agama Islam YDI Lubuk Sikaping, 2026)
This study aims to analyze the program innovations implemented by the Indonesian Mosque Youth Communication Agency (BKPRMI) to attract youth to participate in mosque activities in Medan Denai District. This study uses a descriptive qualitative approach with data collection techniques through in-depth interviews, observation, and documentation. Research informants consisted of BKPRMI administrators at the sub-district level and youth mosque administrators. Data analysis was carried out through the stages of data reduction, data presentation, and systematic conclusion drawing. The results show that BKPRMI innovates through more participatory coaching, the use of digital media, the development of creative and productive activities, and the organization of social and sports activities. These innovations have been proven to increase youth involvement in various mosque activities, although there are still obstacles such as low motivation for some youth, the influence of digital media, time constraints, and limited organizational resources. This study concludes that adaptive, participatory programs that are in accordance with the characteristics of the younger generation can increase youth participation in mosques. These findings contribute to the development of studies on da'wah, Islamic communication, and youth education, particularly regarding innovation strategies for youth mosque organizations in the digital era.